Die altäthiopischen Monatsnamen ägyptisch-koptischer Herkunft: Beispiele wiederholter Entlehnung aus einer sich verändernden Matrixumgebung - Breyer, Francis Amadeus Karl (Aethiopica, 2005)
The amount of different spellings for the Ethiopian month names originally borrowed from Coptic has always been confusing. On a closer look, they can be divided into two groups, whose differences exactly correspond to those between the Coptic dialects Sahidic and Bohairic. Thus, the nouns in question are not only of greatest value for our understanding of Coptic phonology – and through their etymological connections to Old Egyptian even for this very early stage of the language - , they show very clearly, how the successive borrowing of loanwords from changing linguistical environments works. The first Coptic month names were borrowed from the Saidic dialect, but when the patriarch’s see moved from Kairo to Alexandria, the corresponding words were borrowed again, this time from the northern Bohairic dialect. After the Coptic names had been borrowed in Arabic and the Coptic language itself came to be extinct, those words were borrowed a third time, their forms being now taken from Arabic. On the level of phonology, special attention should be given to the consonants, which have been reconstructed as being postglottalized in Old Egyptian, a proposal which is confirmed by the Ethiopian evidence.